Correction: EPR imaging of sinapyl alcohol and its application to the study of plant cell wall lignification. Issue 3 (4th January 2021) - Simon, Clémence; Lion, Cédric; Ahouari, Hania; Vezin, Hervé; Hawkins, Simon; Biot, Christophe
Abstract : Correction for 'EPR imaging of sinapyl alcohol and its application to the study of plant cell wall lignification' by Clémence Simon et al., Chem. Commun., 2021, DOI: ; 10.1039/D0CC05218C .